A Follow-up Study of Electroconvulsive Therapy in Children and Adolescents. Issue 1 (March 2018) - Mitchell, Shanti; Hassan, Ehmer; Ghaziuddin, Neera
Abstract : Objectives: Electroconvulsive therapy (ECT) is an effective and a safe treatment for several severe psychiatric disorders across the age span. However, its use remains controversial and highly stigmatized especially among patients under 18 years. In this study, we examined current symptoms, attitudes, perception, and functioning of patients treated with ECT when they were less than 18 years old. Methods: Participants had received ECT before age 18, between 1989 and 2015, at a tertiary medical center. Institutional review board–approval was obtained, and study documents (cover letter, consent, self-ratings scales for depression, anxiety, global functioning, and suicidality) were mailed. Results: Based on self-rated depression, 59.1% (13/22) participants indicated mild or no depression; 65% (13/20) reported mild or no anxiety; the majority, 84.3% (16/19) perceived ECT as having improved their overall illness; and 27.3% (6/22) among the respondents reported no clinical impairment on a global functioning scale, whereas 72.7% (16/22) reported significant or severe impairment. Despite reports of ongoing impaired global functioning among some participants, adequate academic performance (83.3%, 5/6) and mild or no suicidality (78.3%, 18/23) were endorsed by the majority reported. Conclusions: The majority of participants who had received ECT before age 18 years reported mild or absence of depression and anxiety on self-rated follow-up measures after treatment with ECT. Most notably, the majority reported absence of suicidality and adequate academic performance. A number of respondents, however, continued to endorse global impairment, which may be a reflection of their baseline severe illness, which had warranted treatment with ECT.